The ethics of computer games - Sicart, Miguel, 1978- (MIT Press, 2009)
Miguel Sicart looks at the ethical component in many computer games, including how players may engage their ethical values in gameplay and the implications for game design.
Keywords: Video games -- Moral and ethical aspects.; Video games -- Philosophy.; elektronické knihy; electronic books